2020
DOI: 10.1017/s143192762000015x
|View full text |Cite
|
Sign up to set email alerts
|

Versatile Homebuilt Gas Feed and Analysis System for Operando TEM of Catalysts at Work

Abstract: Understanding how catalysts work during chemical reactions is crucial when developing efficient catalytic materials. The dynamic processes involved are extremely sensitive to changes in pressure, gas environment and temperature. Hence, there is a need for spatially resolved operando techniques to investigate catalysts under working conditions and over time. The use of dedicated operando techniques with added detection of catalytic conversion presents a unique opportunity to study the mechanisms underlying the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 22 publications
(36 citation statements)
references
References 51 publications
(72 reference statements)
0
36
0
Order By: Relevance
“…6, which illustrates the formation and removal of an SMSI induced overlayer on Pt and Pd nanoparticles deposited on TiO 2 supports under different reaction conditions. It should be noted that in all of these works, with the exception of a few operando CO oxidation studies [23,24,100,105,106], catalytic activity is assumed but has not been demonstrated, i.e. catalytic conversion has not been proven in parallel to TEM observations.…”
Section: Gas Cells-on the Relevance Of In Situ Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…6, which illustrates the formation and removal of an SMSI induced overlayer on Pt and Pd nanoparticles deposited on TiO 2 supports under different reaction conditions. It should be noted that in all of these works, with the exception of a few operando CO oxidation studies [23,24,100,105,106], catalytic activity is assumed but has not been demonstrated, i.e. catalytic conversion has not been proven in parallel to TEM observations.…”
Section: Gas Cells-on the Relevance Of In Situ Resultsmentioning
confidence: 99%
“…These CO oxidation studies achieved the simultaneous acquisition of conversion rates and TEM measurements. This is done using a mass spectrometer (MS) connected to the gas outlet of the in situ TEM holder [106] that allows a direct correlation of structure and reactivity and facilitates insights into local structure-function relationships [23,24,100,105,106]. Conversion can also be tracked via EELS analysis of the gas composition as demonstrated by Crozier et al [107,108].…”
Section: Gas Cells-on the Relevance Of In Situ Resultsmentioning
confidence: 99%
See 3 more Smart Citations